Psychometric Properties of the Trail-Making Test in Dementia Population - Wahyudi, Rahmadi Maulana Kusuma; Victoriana, Evany; Kuntari, C.M. Indah Soca R.; Ong, Paulus Anam; Sulastri, Augustina; Luijtelaar, Gilles van (Jurnal Psikologi, 2025)
The trail-making test (TMT) is a commonly used executive function test in various populations worldwide. It is also used to assess the dementia population, who experience impairment in executive function. In Indonesia, the psychometric properties of TMT for local populations have been reported to be satisfactory. However, there was a lack of studies on the validity and reliability of the TMT for the dementia population. In this study, we examined the validity and reliability of TMT and established population-specific norms for dementia. We analyzed data from 71 TMT scores and three other neuropsychological tests (DSST, DS test, and MOCA) to examine its psychometric properties. The internal consistency analysis was used to assess the reliability of the TMT, while the generalized structured component analysis (GSCA) was conducted to examine TMT’s validity in assessing executive function. The reliability test indicated that the TMT has high reliability (ω = 0.639), while GSCA revealed that TMT has high construct validity with three other neuropsychological tests (TMT-A=0.72 and TMT-B=0.573). Additionally, this study provides standardized norms of TMT for the dementia population.